COMPARISON OF 40AR-39AR AND RB-SR DATA ON PHENGITES FROM THE UHP BROSSASCO-ISASCA UNIT (DORA MAIRA MASSIF, ITALY): IMPLICATIONS FOR DATING WHITE MICA - Di Vincenzo G.; Tonarini S.; Lombardo B.; Castelli D.; Ottolini L. (My University, 2006)
Different lithologies (impure marble, eclogite and granitic orthogneiss) sampled from a restricted area of the coesite-bearing Brossasco–Isasca Unit (Dora Maira Massif) have been investigated to examine the behaviour of 40Ar–39Ar and Rb–Sr systems in phengites developed under ultrahigh-pressure (UHP) metamorphism. Mineralogical and petrological data indicate that zoned phengites record distinct segments of the P–T path: prograde, peak to early retrograde in the marble, peak to early retrograde in the eclogite, and late retrograde in the orthogneiss. Besides major element zoning, ion microprobe analysis of phengite in the marble also reveals a pronounced zoning of trace elements (including Rb and Sr). 40Ar–39Ar apparent ages (?35–62?Ma, marble; ?89–170?Ma, eclogite; ?35–52?Ma, orthogneiss), determined through Ar laserprobe data on phengites (step-heating and in situ techniques), show wide intra-sample and inter-sample variations closely linked to within-sample microchemical variations: apparent ages decrease with decreasing celadonite contents. These data confirm previous reports on excess Ar and, more significantly, highlight that phengite acted as a closed system in the different lithologies and that chemical exchange, not volume diffusion, was the main factor controlling the rate of Ar transport. Conversely, a Rb–Sr internal isochron from the same eclogite yields an age of ?36?Ma, overlapping with the time of the UHP metamorphic peak determined through U–Pb data and thereby corroborating the previous conclusion that UHP metamorphism and early retrogression occurred in close succession. Different phengite fractions of the marble yield calcite–phengite isochron ages of ?36 to ?60?Ma. Although this time interval matches Ar ages from the same sample, Rb–Sr data from phengite are not entirely consistent with the whole dataset. According to trace element variations in phengite, only Rb–Sr data from two wet-ground phengite separates, yielding ages of ?36 and ?41?Ma, are internally consistent. The oldest age obtained from a millimetre-sized grain fraction enriched in prograde–peak phengites may represent a minimum age estimate for the prograde phengite relics. Results highlight the potential of the in situ 40Ar–39Ar laser technique in resolving discrete P–T stages experienced by eclogite-facies rocks (provided that excess Ar is demonstrably a negligible factor), and confirm the potential of Rb–Sr internal mineral isochrons in providing precise crystallization ages for eclogite-facies mineral assemblages.
Keywords: 40Ar–39Ar dating; Rb–Sr dating; phengite; SIMS; UHP metamorphism